2010
DOI: 10.1007/978-3-642-14998-6_104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on the Performance of Footwear Foams: Review of Developments

Abstract: Abstract--The human foot is a multifunctional system that serves as the primary physical interaction between the body and the environment during gait. Footwear foam components maintain efficient foot function which is essential for daily living and provide cushioning by acting as a protective layer between the foot and the ground that attenuates the shock of impact. Footwear foam materials have high temperature dependency mechanical characteristics. The lower the temperature, the less elastic the material beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…These findings indicated that runners might be subjected to a higher injury risk when running in extremely high temperatures, possibly because the shoe integrity becomes less stable. It has been shown that when footwear midsole EVA foam reaches a temperature of 70 • C, the material begins to dissolve [12]. The midsole temperature of each shoe worn by the participants exceeded 70 • C; thus, the cushioning capability of the EVA shoes is degrading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicated that runners might be subjected to a higher injury risk when running in extremely high temperatures, possibly because the shoe integrity becomes less stable. It has been shown that when footwear midsole EVA foam reaches a temperature of 70 • C, the material begins to dissolve [12]. The midsole temperature of each shoe worn by the participants exceeded 70 • C; thus, the cushioning capability of the EVA shoes is degrading.…”
Section: Discussionmentioning
confidence: 99%
“…2023, 13, 8024 2 of 12 brand new footwear [11]. However, it should be noted that the mechanical parameters of a running shoe can also be altered when used in extreme weather conditions [12]. Cook et al [13] demonstrated that running shoes containing air wedges, fiberglass plates and molded and composite midsole materials can preserve approximately 67% of their original shock absorption capability after 160-240 km using continuous machine-simulated mileage testing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of these materials in SA and protective equipment largely depends on maintaining the appropriate temperature during their usage. Past investigations have demonstrated that a substantial elevation in the temperature of EVA footwear can lead to a notable surge in the vulnerability to lower limb injuries when individuals partake in physical activities ( Shariatmadari et al, 2010 ). It's worth noting that M. Hojjat et al observed that the rheological properties of non-Newtonian fluids exhibited shear-thinning behavior following an increase in temperature ( Hojjat et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%